2020
DOI: 10.1136/thoraxjnl-2019-213738
|View full text |Cite
|
Sign up to set email alerts
|

Role of unfolded proteins in lung disease

Abstract: The lungs are exposed to a range of environmental toxins (including cigarette smoke, air pollution, asbestos) and pathogens (bacterial, viral and fungal), and most respiratory diseases are associated with local or systemic hypoxia. All of these adverse factors can trigger endoplasmic reticulum (ER) stress. The ER is a key intracellular site for synthesis of secretory and membrane proteins, regulating their folding, assembly into complexes, transport and degradation. Accumulation of misfolded proteins within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 103 publications
(109 reference statements)
1
31
0
Order By: Relevance
“…However, these antiviral therapies do not take into account that the pathophysiology associated with COVID-19 is mostly related to an aberrant cellular response. In some clinical manifestations of COVID-19, an exacerbated UPR could play a key role [86–88]. For example, activation of ER stress and the UPR is one of the major triggers of endothelial dysfunction [89, 90], which is associated with acute respiratory distress syndrome (ARDS) [91], a diffuse inflammatory lung injury present in 20-67% of hospitalised patients [92, 93].…”
Section: Discussionmentioning
confidence: 99%
“…However, these antiviral therapies do not take into account that the pathophysiology associated with COVID-19 is mostly related to an aberrant cellular response. In some clinical manifestations of COVID-19, an exacerbated UPR could play a key role [86–88]. For example, activation of ER stress and the UPR is one of the major triggers of endothelial dysfunction [89, 90], which is associated with acute respiratory distress syndrome (ARDS) [91], a diffuse inflammatory lung injury present in 20-67% of hospitalised patients [92, 93].…”
Section: Discussionmentioning
confidence: 99%
“…However, these antiviral therapies do not take into account that the pathophysiology associated with COVID-19 is mostly related to an aberrant cellular response. In some clinical manifestations of COVID-19, an exacerbated UPR could play a key role [94][95][96]. For example, activation of ER stress and the UPR is one of the major triggers of endothelial dysfunction [97,98], which is associated with acute respiratory distress syndrome (ARDS) [99], a diffuse inflammatory lung injury present in 20-67% of hospitalised patients [100,101].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…A previous study reported that EIF2 signaling was downregulated in patients with childhood asthma (29). Moreover, pathways associated with ER stress and UPR play a role in modulating inflammatory and immune responses in the development of severe asthma (30). Furthermore, administration of the ER stress inhibitor decreased the IL-17 expression (31).…”
Section: Discussionmentioning
confidence: 95%